COVID-19 and Preexisting Comorbidities: Risks, Synergies, and Clinical Outcomes - Bigdelou, Banafsheh; Sepand, Mohammad Reza; Najafikhoshnoo, Sahar; Negrete, Jorge Alfonso Tavares; Sharaf, Mohammed; Ho, Jim Q; Sullivan, Ian; Chauhan, Prashant; Etter, Manina; Shekarian, Tala; Liang, Olin; Hutter, Gregor; et al. (Frontiers in immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its associated symptoms, named coronavirus disease 2019 (COVID-19), have rapidly spread worldwide, resulting in the declaration of a pandemic. When several countries began enacting quarantine and lockdown policies, the pandemic as it is now known truly began. While most patients have minimal symptoms, approximately 20% of verified subjects are suffering from serious medical consequences. Co-existing diseases, such as cardiovascular disease, cancer, diabetes, and others, have been shown to make patients more vulnerable to severe outcomes from COVID-19 by modulating host-viral interactions and immune responses, causing severe infection and mortality. In this review, we outline the putative signaling pathways at the interface of COVID-19 and several diseases, emphasizing the clinical and molecular implications of concurring diseases in COVID-19 clinical outcomes. As evidence is limited on co-existing diseases and COVID-19, most findings are preliminary, and further research is required for optimal management of patients with comorbidities.
Keywords: cancer; coronavirus disease 2019; Communicable Disease Control; cardiovascular disease; kontrola infekčních nemocí; karanténa; COVID-19; Pandemics; Humans; pandemie; treatment implications; diabetes; immune responses; Quarantine; lidé; SARS-CoV-2